Model Predictive Control of Cascaded Multi-Output Multilevel Converter - Jayan, Vijesh (2022)
The paper presents a novel cascaded multi-output multilevel (CMOM) converter topology. The structure is composed of m converters that contain multiple n output voltage terminals. The proposed cascaded multilevel converter can provide multiple independent output voltages, and each output voltage can generate 2m+1 voltage levels. The output voltages are controlled in-terms of amplitude, frequency and phase angle independently. The mathematical model is developed for m = 2 converters with n = 2 output voltage terminals and is used in model predictive control (MFC) algorithm to optimize the control objectives. Thus the model can provide two different output voltages, each of which can generate up to five voltage levels. The performance is evaluated and demonstrated using MATLAB simulation results.